The impact of home and host country institutional development on multinationals' R&D intensity - Pia Ellimäki; Nuria Esther Hurtado-Torres; Eulogio Cordón-Pozo (BRQ Business Research Quarterly, 2024)
This empirical article examines how the institutional development of the home country and host countries in which multinational enterprises (MNEs) are embedded can drive MNEs' research and development (R&D) intensity. In doing so, this study analyzes 967 firm-year observations of 234 pharmaceutical firms from 30 developed and less developed countries in the period from 2010 to 2017. We find empirical support for internationalization toward developed countries as a driver of R&D intensity at the firm level. Furthermore, we find that this positive effect is stronger for MNEs from less institutionally developed home countries. The results can help managers, researchers, and policymakers to better understand the innovation process in R&D-intensive industries.
Keywords: M16; O32; 650; R&D intensity; innovation; institutional development; home country; host countries; internationalization